2022
DOI: 10.1016/j.ophtha.2021.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Re: Chiang et al.: International Classification of Retinopathy of Prematurity, Third Edition (Ophthalmology. 2021;128:e51–e68)

Abstract: TO THE EDITOR: In their article, Chiang et al 1 have updated the International Classification of Retinopathy of Prematurity (ICROP) to improve objectivity of finding, as well as to encompass clinical variations observed in regression or reactivation of retinopathy of prematurity (ROP), particularly after treatment with anti-vascular endothelial growth factor. The authors have subclassified zone II as anterior and posterior to identify the more serious disease in posterior zone II. However, the standard of care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 5 publications
0
70
0
Order By: Relevance
“…The most common indication was type 1 ROP in zone I of any stage with or without plus disease (7 documents). 25,2830,32,42,43 In other countries, anti-VEGF agents were also recommended for other indications, including: stage 3 with plus ROP in zone I, 26,33 type 1 ROP in zone I when laser therapy fails 31 or is contraindicated, 38 type 1 ROP in any zone when laser therapy fails 32,35 or is contraindicated, 29,32,35,38,40 type 1 ROP in any zone when primary laser 28 or surgical treatment 32 are not available, type 1 ROP in any zone in stage 4–5 with vitreoretinal membranes, 33 any case of aggressive ROP (A-ROP) 29,32,33,40,42,50 or only when laser therapy fails. 31 Some authors recommended using anti-VEGF agents in type 1 ROP involving zone II and III 43 or posterior zone II with or without plus disease 29 or only when plus disease is present.…”
Section: Resultsmentioning
confidence: 99%
“…The most common indication was type 1 ROP in zone I of any stage with or without plus disease (7 documents). 25,2830,32,42,43 In other countries, anti-VEGF agents were also recommended for other indications, including: stage 3 with plus ROP in zone I, 26,33 type 1 ROP in zone I when laser therapy fails 31 or is contraindicated, 38 type 1 ROP in any zone when laser therapy fails 32,35 or is contraindicated, 29,32,35,38,40 type 1 ROP in any zone when primary laser 28 or surgical treatment 32 are not available, type 1 ROP in any zone in stage 4–5 with vitreoretinal membranes, 33 any case of aggressive ROP (A-ROP) 29,32,33,40,42,50 or only when laser therapy fails. 31 Some authors recommended using anti-VEGF agents in type 1 ROP involving zone II and III 43 or posterior zone II with or without plus disease 29 or only when plus disease is present.…”
Section: Resultsmentioning
confidence: 99%
“…All included premature infants were examined by RetCam- II fundus digital camera, and the ROP condition was graded according to the International Classification of ROP (ICROP). 7 Treatment indications were carried out in accordance with the standard of Early Treatment for ROP Collaborative Group (ET-ROP), 10 and the treatment objects included: (1) Threshold lesions: Stage 3 lesions in Zone I and Zone II for 5 consecutive hours or 8 cumulative hours, Simultaneously with Plus lesions. (2) Pre-threshold lesions Type 1: ROP of each stage in Zone I with plus lesions, or Stage 3 lesions without plus lesions, or Stage 2 or 3 ROP in zone II with plus lesions.…”
Section: Methodsmentioning
confidence: 99%
“…6 In the current international classification standards, the severity of retinopathy is mainly described according to the degree and extent of abnormal vascular proliferation and the presence of additional lesions. 7…”
mentioning
confidence: 99%
“…79 Although Zone Ⅰ subgroups have not been defined in the ICROP reports, the definition of posterior zone Ⅰ was designated for eyes with a posterior border of retinal vascularization that is shorter than the optic disc-to-fovea distance (ODFD). 9,10…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Although Zone Ⅰ subgroups have not been defined in the ICROP reports, the definition of posterior zone Ⅰ was designated for eyes with a posterior border of retinal vascularization that is shorter than the optic disc-to-fovea distance (ODFD). 9,10 In studies evaluating posterior zone Ⅰ eyes as a subgroup, it has been reported that the majority of the posterior Tertiary ROP Clinic, Health Science University Kanuni Sultan Suleyman Training and Research Hospital, Istanbul, Turkey zone Ⅰ cases have unfavorable anatomical results after laser treatment. 9,11 Although better anatomic and refractive results have been reported in zone Ⅰ with intravitreal bevacizumab (IVB) in many reports, as far as we know, the outcomes of posterior zone Ⅰ cases with IVB treatment have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%